Hermeneutic Questions in Organizational Studies: two interpretative possibilities for research - Vieira, Almir Martins; Rivera, Dario Paulo Barrera (Review of Business Management, 2012)
The present text has the objective of presenting theoretical considerations regarding two types of strategy of research: phenomenology and ethnography. Based on a hermeneutic approach, the two conceptual propositions are presented, the first being dealt with in the sociological context, and the second presented as an anthropological basis. Their similar uses in an organizational context - as well as their differences – are highligthed according to the theoretical contributions of authors belonging to the qualitative universe of organizational research. The text reveals, by the presentations of reported theoretical assumptions, the relevance of the interpretative perspective for the conduction of research that has the organization as object of study, in the pursuit of the identification of ways of constructing the social reality that is the result of the analysis of meanings and experiences lived by the participants, highlighting the importance of the bond between researcher and the research object The theoretical discussion regarding the two perspectives allows to observe the competence of the phenomenological and ethnographic research practice within the field of organizational studies, showing their methodological possibilities to identify dynamics that relate to the experience of life, favoring the analysis of the human being as a phenomenon of interpretation. Key words: Hermeneutic. Phenomenology. Ethnography.